Editorial - Thomas Wilson (Information Research: An International Electronic Journal)
With this issue we come to the end of the 28th year of publication of Information Research. The journal was founded at a time a significant change in the information world, with the Internet and the World Wide Web being in the early stage of development, with the iPhone, the iPad, and social media yet to be invented. Now this year has seen the emergence of generative artificial intelligence and, just as 1995 was a transition point, in the move from print to digital, so this year is a transition point – in the move from what is still, very largely, a combination of human and computer to generate services, to a future of human and AI system of service delivery. And, perhaps, before too long, artificial intelligence acting alone.